2012
DOI: 10.1068/p7278
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Ethnicity Face Shape and Attractiveness in Humans

Abstract: Abstract. Many studies show agreement within and between populations and cultures for general judgments of facial attractiveness. Studies that have examined the attractiveness of specific traits have also highlighted cross-cultural differences for factors such as symmetry, averageness, and masculinity. One trait that should be preferred across cultures is heterozygosity. Indeed, several studies suggest that mixed ethnicity, in terms of appearing to possess a mixture of traits from different human population gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…; Lewis ; Little et al . ). In addition, work using facial image manipulations demonstrated that cues to heterozygosity are themselves attractive independent of other accompanying indicators of heterosis (Lewis ; Little et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Lewis ; Little et al . ). In addition, work using facial image manipulations demonstrated that cues to heterozygosity are themselves attractive independent of other accompanying indicators of heterosis (Lewis ; Little et al .…”
Section: Discussionmentioning
confidence: 97%
“…Facial attractiveness may be a particularly effective indicator of health and condition, and of individual heterozygosity (Roberts et al 2005b;Lie et al 2008). To illustrate, the faces of mixed-ethnicity individuals, who tend to be more heterozygous than average, have been shown to be more attractive than single-ethnicity faces across genders and cultures (Rhodes et al 2005;Lewis 2010;Little et al 2012). In addition, work using facial image manipulations demonstrated that cues to heterozygosity are themselves attractive independent of other accompanying indicators of heterosis (Lewis 2010;Little et al 2012).…”
Section: Humans Select More Mhc-diverse Matesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a missed opportunity. An obvious suggestion would be to extend the research of Lewis [210] and Little et al [211], who reported that individuals of mixed-ethnicity are considered more attractive than those of relatively "pure" ethnicity. Is part of the attraction due to increased facial symmetry?…”
Section: Outbreeding Depression Heterosis and Genomic Coadaptationmentioning
confidence: 99%
“…This is not a refutation of heterozygosity and attractiveness. 13 There can be a national (France) or regional (East Asia) average that is not exactly the sameness of one's social group. Although we are at it, can we stop referring to all people of the area of the Earth formerly referred to as the Orient as Asian?…”
mentioning
confidence: 99%